International Debt Statistics 2015 - World Bank Group (Washington, DC: World Bank, 2014)
International Debt Statistics (IDS) 2015 is a continuation of the World Bank’s Global Development Finance publication, Volume II (1997 through 2009) and the earlier World Debt Tables (1973 through 1996). IDS 2015 provides statistical tables showing the external debt of 128 developing countries that report public and publicly guaranteed external debt to the World Bank’s Debtor Reporting System (DRS). It also includes tables of key debt ratios for individual reporting countries and the composition of external debt stocks and flows for individual reporting countries and regional and income groups along with some graphical presentations.